Evaluasi Distribusi Air Baku Pada Waduk Wonosari di Kabupaten Bengkalis - Randhi Saily; Ahmad Hamidi (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2020)
Wonosari Reservoir in Bengkalis Regency as a source of raw water to serve some residents of Bantan and Bengkalis districts. The volume of water in this reservoir has decreased annually due to the buildup of sedimentation. This research aims to analyze the relationship between raw water demand which is directly proportional with the projection of population growth and the availability of water in the Wonosari reservoir. The results of research conducted observational, in 2030 indicated a shortage of raw water with needs in Bantan and Bengkalis districts of 64.16 lt / sec and 215.96 lt/sec or equivalent with 5543.74 m3/day and 18658.09 m3/day which are the total of 24201.83 m3/day, while the availability of water is 94585.35 m3 and continues to decrease. Based on this analysis, it is necessary to anticipate the achievement of solutions to water availability so that needs can be met.